Abdominal Wound Dehiscence: A Review of Risk Factors, Prevention and Management in Obstetrics and Gynecology Practice - Hermawan, Gezta Nasafir; Wibisono, Jacobus Jeno; Nembo, Lidya F (Medicinus, 2021)
Abdominal wound dehiscence (AWD) is considered as a severe postoperative complication in which there is a partial or complete disruption of an abdominal wound closure with or without protrusion and evisceration. The incidence and mortality rate varies in different health centers. Risk factors are classified into three groups, which includes: pre-operative, intra-operative, and post-operative. The management of Burst Abdomen or Wound Dehiscence is diverse from conservative treatment to surgical treatment.